Association of Opioids with Falls, Fractures, and Physical Performance among Older Men with Persistent Musculoskeletal Pain - Krebs, Erin E. (J Gen Intern Med, 2016)
BACKGROUND: Although older adults are disproportionately affected by painful musculoskeletal conditions and receive more opioid analgesics than persons in other age groups, insufficient evidence is available regarding opioid harms in this age group. OBJECTIVE: To examine longitudinal relationships between opioid use and falls, clinical fractures, and changes in physical performance. We hypothesized that opioid use would be associated with greater risks of falling and incident clinical fractures and greater declines in physical performance. DESIGN: We analyzed data from the Osteoporotic Fractures in Men Study (MrOS), a large prospective longitudinal cohort study. Participants completed baseline visits from 2000 to 2002 and were followed for 9.1 (SD 4.0) years. PARTICIPANTS: MrOS enrolled 5994 community-dwelling men ≥ 65 years of age. The present study included 2902 participants with back, hip, or knee pain most or all of the time at baseline. MAIN MEASURES: The exposure of interest was opioid use, defined at each visit as participant-reported daily or near-daily use of any opioid-containing analgesic. Among patients, 309 (13.4 %) reported opioid use at one or more visits. Participants were queried every 4 months about falls and fractures. Physical performance scores were derived from tests of grip strength, chair stands, gait speed, and dynamic balance. KEY RESULTS: In the main analysis, the adjusted risk of falling did not differ significantly between opioid use and non-use groups (RR 1.10, 95 % CI 0.99, 1.24). Similarly, adjusted rates of incident clinical fracture did not differ between groups (HR 1.13, 95 % CI 0.94, 1.36). Physical performance was worse at baseline for the opioid use group, but annualized change in physical performance scores did not differ between groups (−0.022, 95 % CI −0.138, 0.093). CONCLUSIONS: Additional research is needed to determine whether opioid use is a marker of risk or a cause of falls, fractures, and progressive impairment among older adults with persistent pain.